A STUDY OF COLONIAL INSCRIPTIONS IN STOVIA SALEMBA: THE MARKER OF MEDICAL EDUCATION DEVELOPMENT IN DUTCH EAST INDIES - Fitri, Zulfa Nurdina (UI Scholars Hub, 2023)
STOVIA serves as a starting point of medical education in Indonesia and is interesting for historical study, especially after the discovery of inscriptions. This inscription consists of different letters and languages and, despite its limited information, clearly plays a pivotal role as a means of communication in its era. Inscriptions are considered the most reliable data source as they are made in their era and need to be studied, transliterated, and translated. This paper reviews two inscriptions found in STOVIA Salemba: the groundbreaking and the building inauguration and appreciation for one of the directors of STOVIA, dr. J. Noordhoek Hegt. This study was conducted to extract the information from the inscription to allow the community learns from its content. This paper also discusses the role of the colonial inscription as the marker of medical institution development in the Dutch East Indies.